Emergetic and cosmic exergy-based ecological assessments of long-term raised field eco-farming systems in saline–alkaline lands. (June 2021) - Hu, Hengyu; Zhang, Mengkun; Zhang, Yin; Fu, Min; Chen, Jiansheng; Li, Geng; Zhai, Mingzhen; Ming, Xiuyun; Ning, Tangyuan
Highlights: The electrical conductivity in topsoil was reduced by using raised field. Emergetic and cosmic exergy-based ecological assessments were used. The superior agricultural system has the highest renewability and sustainability. The economic benefit of the superior agricultural system was the highest. Abstract: The ecological and efficient use of saline–alkaline lands is very important worldwide. The main objective of this paper is to identify an eco-farming system suitable for saline–alkaline lands via emergetic and cosmic exergy-based ecological assessments. Three ecosystems were compared: an agriculture-free system, a local agricultural system, and a superior agricultural system. In the latter two systems, crops (winter wheat and summer maize), animal husbandry and orchards were integrated in raised fields. In the superior agricultural system, conservation tillage, intercropping, and farming-grazing system were used. After 15 years, the electrical conductivity of the soil in 0–30 cm depth was 49.2% reduced using the raised field. In 2018, the average soil electrical conductivity of the superior agricultural system was 20.1% and 14.8% lower than that of the agricultural-free system and local agricultural system, respectively. The superior agricultural system was more sustainable than both the agriculture-free system and the local agricultural system by the footprint investment per unit of footprint delivered method. The renewability and sustainability of the superior agricultural system were higher than the other systems. The economic benefit of the superior agricultural system was the highest among the three systems, which is 1.34 times higher than that of the local agricultural system. These results suggest that the superior agricultural system is better than the other two systems because it promotes the flow of materials and energy and takes advantage of the mutually beneficial effects by using conservation tillage, intercropping, and farming-grazing system. This study contributes to the theoretical foundation for policy-making in saline–alkaline regions worldwide.